Dramaturgia de autoria feminina contemporânea paranaense: estéticas de (re)existências - Gomes, Sumara (2021)
The dissertation focuses on the research of theatrical texts of female authors, looking to reflect on the poetic discourse of playwrights that lived in the state of Paraná and have had written texts for theater in the last decades. It brings the voices of women who writes and wrote for theater in Brazil and the world, to endorse the dramaturgical researches of these new authors, as well as the voices of authors who contribute theoretically to the contemporary theater writing, in addition to feminist voices that discuss the panorama of the movement and how it influences writing for theater made by women. The research includes the study of texts by Leilah Assunção, from the 1960s, Grace Passô, contemporary, from the Rio-São Paulo axis, and Lígia Souza Oliveira, Juliana Partyka and Patrícia Kamis, playwrights from the Sesi Dramaturgy Center - PR. The choice of these three authors in the context of the universe that was based on this studied was due to their consistent production, due to the fact that there protuction setting of their pieces that are recognized is the theme that is surround by this dissertation. This is a bibliographic research, of an analytical type, based on comparative studies in literature and dramaturgy, especially considering the dramaturgical text and its transformations, from Peter Szondi (2001), Jean-Pierre Sarrazac (2012), Hans-Thies Lehmann (2007), Anne Ubersfeld (2005), Jean-Pierre Ryngaert (1998), Sábato Magaldi (2001), Patrice Pavis (2008), Décio de Almeida Prado (2003), Jean-Jacques Roubine (1998), Paul Zumthor (2014), Bertolt Brecht (2005), Peter Brook (1970), J. Guinsburg (2010), Renata Pallottini (1988, 2013), Anne Ubersfeld (2005). Considering studies of dramaturgical production of female authorship in relation to post-colonial studies, we seek theoretical-critical support in authors such as Simone de Beauvoir (1970), Virginia Woolf (1985), Mary Del Priore, (1997), Judith Butler (2003) , Gayatri Spivak (2010), Heloísa Buarque de Hollanda (2019), Elza Cunha de Vincenzo (1992), Djamila Ribeiro (2017), bell hooks (2018), Angela Davis (2016), among others.